Traumatic perforations of tympanic membrane: our experience - Bhargava, Anuja; Faiz, Syed M.; Shakeel, Mohammad; Singh, Nafas J.; Gaurav, Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The aim of the study was to evaluate various etiological factors, clinical presentation in patients presenting with Traumatic ear perforations. Methods: 27 patients were taken in our study who reported within two weeks of history of trauma with no previous history of middle ear pathology. Data was collected and patients were treated. Results: 27 patients were studied (11 males and 16 females); age ranging from 15 years to 56 years. Laterality of trauma was found to be more in left ear. Aural Fullness & pain in ear were the most common presenting complaints. Most common etiology was found to be assault and poster inferior quadrant was found to be most commonly involved. Conclusions: Traumatic perforations have a very good prognosis if they are treated at the right time. We would also like to stress on the fact that domestic violence is still prevalent in our society leading to patients of traumatic perforation.